(3TQM RGO GdeSGaQ deYQag aVd hVY GdOGFQs - (3eMeO GdNVQi GdOejGWis; (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3gPG eG OYJ Edjg MGLg GdeJagejf Edi RGO GdeSGaQ ai eYQag hVY aVd GdOGFQ GdJi hVYgG TgGH GdOjf Hf CMeO Hf GdeLOi ef TQM jMd CdaGXgG s
(3BNQgG (B:s
(3hdfMHS gfG YfGf Gdbde hfMeO Gddg s
(3ajgG QShe cKjQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B67 s
Keywords: (3Gdadcs